Hydrodynamic performance and surface characterisation of antifouling coatings after long-term marine exposure - E. Begovic; G. Assanelli; F. Aiello; A. Amico; A. Amoresano; G. Battaglia; C. Bertorello; L. Bonoldi; M. Bruscagin; F. De Luca; G. Fiori; C. Fontanarosa; et al. (Ocean Engineering, 2026)

Workflow for the Creation of 3D Stereoscopic Models of Supra- and Infratentorial Brain Venous Anatomy and their Integration in a Virtual Reality Environment - Francesco Carbone; Toma Spiriev; Martin Trandzhiev; Michael Wolf-Vollenbröker; Kay M. Körner; Andrea Steuwe; Matteo de Notaris; Vladimir Nakov; Jan F. Cornelius (Neuroinformatics, 2025)

Challenges of accounting nitrous oxide emissions from agricultural crop residues - Jørgen E. Olesen; Robert M. Rees; Sylvie Recous; Marina A. Bleken; Diego Abalos; Ishita Ahuja; Klaus Butterbach‐Bahl; Marco Carozzi; Chiara De Notaris; Maria Ernfors; Edwin Haas; Sissel Hansen; et al. (Global Change Biology, 2023)
Crop residues are important inputs of carbon (C) and nitrogen (N) to soils and thus directly and indirectly affect nitrous oxide (N 2 O) emissions. As the current inventory methodology considers N inputs by crop residues as the sole determining factor for N 2 O emissions, it fails to consider other underlying factors and processes. There is compelling evidence that emissions vary greatly between residues with different biochemical and physical characteristics, with the concentrations of mineralizable N and decomposable C in the residue biomass both enhancing the soil N 2 O production potential. High concentrations of these components are associated with immature residues (e.g., cover crops, grass, legumes, and vegetables) as opposed to mature residues (e.g., straw). A more accurate estimation of the short‐term (months) effects of the crop residues on N 2 O could involve distinguishing mature and immature crop residues with distinctly different emission factors. The medium‐term (years) and long‐term (decades) effects relate to the effects of residue management on soil N fertility and soil physical and chemical properties, considering that these are affected by local climatic and soil conditions as well as land use and management. More targeted mitigation efforts for N 2 O emissions, after addition of crop residues to the soil, are urgently needed and require an improved methodology for emission accounting. This work needs to be underpinned by research to (1) develop and validate N 2 O emission factors for mature and immature crop residues, (2) assess emissions from belowground residues of terminated crops, (3) improve activity data on management of different residue types, in particular immature residues, and (4) evaluate long‐term effects of residue addition on N 2 O emissions.

Norfloxacin prophylaxis effect on multidrug resistance in patients with cirrhosis and bacterial infections - Sebastián Marciano; Maria N. Gutierrez-Acevedo; Sabrina Barbero; Lorena del C. Notari; Marina Agozino; Jose L. Fernandez; Maria M. Anders; Nadia Grigera; Florencia Antinucci; Orlando F. Orozco Ganem; Maria D. Murga; Daniela Perez; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)